2003
DOI: 10.1242/jcs.00301
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular calcium measurements of single human skin cells after stimulation with corticotropin-releasing factor and urocortin using confocal laser scanning microscopy

Abstract: Using confocal laser scanning microscopy we investigated the Ca2+ distribution in single corticotropin releasing factor- and urocortin-stimulated human skin cells. The models tested included melanoma cells, neonatal melanocytes and keratinocytes, and immortalized HaCaT keratinocytes. The changes in intracellular Ca2+ signal intensities observed after stimulation of different cell types with corticotropin releasing factor and urocortin showed that: (1) the increase of intracellular Ca2+ concentration was caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 54 publications
3
49
1
Order By: Relevance
“…CRH also stimulated IP 3 production in all the tested skin cells (melanocytes, keratinocytes and fibroblasts) (22,23). Taken together, the data (6,7,12,(22)(23)(24)(25)39) indicate that increases in intracellular Ca 2+ concentrations are induced by two mechanisms: a) stimulation of IP 3 , which activates release of Ca 2+ from intracellular stores; and b) direct coupling to voltage-activated Ca 2+ ion channels, whose opening leads to rapid cytosolic Ca 2+ influx. We also found that CRH induced the production of cAMP in skin cells expressing CRH-R1alpha.…”
Section: Second Messengersmentioning
confidence: 58%
See 2 more Smart Citations
“…CRH also stimulated IP 3 production in all the tested skin cells (melanocytes, keratinocytes and fibroblasts) (22,23). Taken together, the data (6,7,12,(22)(23)(24)(25)39) indicate that increases in intracellular Ca 2+ concentrations are induced by two mechanisms: a) stimulation of IP 3 , which activates release of Ca 2+ from intracellular stores; and b) direct coupling to voltage-activated Ca 2+ ion channels, whose opening leads to rapid cytosolic Ca 2+ influx. We also found that CRH induced the production of cAMP in skin cells expressing CRH-R1alpha.…”
Section: Second Messengersmentioning
confidence: 58%
“…In the case of normal human epidermal keratinocytes, the lack of CRH/ urocortin-induced production of cAMP (22) together with lack of effect of PKA inhibitors on CRH induced keratinocyte differentiation program (23) indicates poor coupling of CRHR1alpha to G s in these cells. In SKMEL-188 melanoma cells, which only express the CRHR1d isoform, the lack of coupling to cAMP with overt stimulation of Ca 2+ flux suggests that the CRH-R1d signal transduction pathway is only coupled to either voltage-activated Ca 2+ ion channels or PLC (12,15,22,25,39). 5.2.3.…”
Section: Second Messengersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the human skin, CRH-R1 is predominantly expressed in the epidermis with CRH-R1α being the major isoform present (Slominski et al, 2004a). The cutaneous CRH-R1 is activated by CRH or urocortin and its intracellular signal transduction pathways are coupled to cAMP, IP3 or Ca (Fazal et al, 1998;Slominski et al, 2006b;Slominski et al, 1999c;Slominski et al, 2000e;Wiesner et al, 2003;Zbytek and Slominski, 2005). UV radiation and factors raising intracellular cAMP increase CRH-R1α expression and change the pattern of isoform expression Slominski et al, 2001).…”
Section: Cutaneous Crh Signaling Systemmentioning
confidence: 99%
“…However, our results are inconsistent with some previous reports. It was found that urocortin, another Urocortin 2 inhibits [Camember of CRF family, stimulated Ca 2 + uptake in skin cells (Wiesner et al, 2003). In addition, urocortin-induced increase of ANP and BNP secretion was completely abolished by a-helical CRF, a specific CRFR2 antagonist, and partially inhibited by diltiazem, another L-type VGCC blocker in cultured neonatal cardiomyocytes (Ikeda et al, 1998).…”
Section: Urocortin 2 Inhibits [Ca 2 + ] I In Pc12 Cells J Tao Et Almentioning
confidence: 99%